Cities with forking paths? - Donovan, Stuart,Graaff, Thomas de,Grimes, Arthur L.,Groot, Henri L. F. de,Maré, David C. (Tinbergen Institute, 2021)
We consider whether external urban economic advantages (agglomeration economies) vary with time and space using a simple economic model and detailed micro-data on 134 locations in New Zealand for the period 1976-2018. We find subtle temporal variation, with estimates peaking in 1991 and then falling over the next 15-years by approximately 1%. Since 2006, however, estimates have remained broadly stable. Our results reveal more significant spatial variation: Large cities offer net benefits in production, but not in consumption, whereas small locations close to large cities (
10419/248768
Keywords: Graue Literatur; agglomeration economies; cities; productivity; consumption; New Zealand